THE SPECIFITIES OF LEXICOGRAPHY, STYLISTICS, THEORY OF TRANSLATION AND METHODS OF TEACHING (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article delves into the distinct realms of linguistics through an exploration of four pivotal subjects: lexicography, stylistics, theory of translation, and methods of teaching. Each subject is meticulously dissected, highlighting its specificities, methodologies, and contributions to our understanding and utilization of language. The annotation provides a succinct yet comprehensive overview of each subject, elucidating the specialized focus areas and unique characteristics that define them. It outlines the intricate nature of lexicography, emphasizing its attention to word meaning, origins, and the meticulous construction of dictionaries. Similarly, the discussion on stylistics illuminates the interplay between language choices, styles, and their impact on communication, drawing from multiple disciplines to dissect linguistic aesthetics.